THE EFFECT OF “PLEASE” STRATEGY ON STUDENTS' WRITING COMPETENCY AT TENTH GRADE OF SMA NEGERI 1 SUKASADA IN ACADEMIC YEAR 2016/2017 - ., Putu Amelia Wardani; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk menivestigasi apakah ada perbedaan yang signifikan dalam kemampuan menulis antara siswa yang diajar menggunakan strategi “PLEASE” dan siswa yang diajar menggunakan strategi menulis konvensional. Penelitian ini merupakan penelitian eksperimen dengan desain Post-test Only Control Group. Populasi terdiri dari siswa kelas sepuluh SMA Negeri 1 Sukasada pada tahun ajaran 2016/2017 dengan 44 siswa sebagai sample yang dipilih menggunakan teknik random sampling. Data dikumpulkan dengan menggunakan writing competency test. Data yang terkumpul dianalisis dengan menggunakan t-test yang dibantu dengan SPSS 19.0. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan terhadap kemampuan menulis antara siswa yang diajar menggunakan strategi “PLEASE” dan siswa yang diajar menggunakan strategi menulis konvensional (tobs = 12.506, p < 0.05) dimana pencapaian siswa yang diajar menggunakan strategi “PLEASE” lebih baik dalam kemampuan menulis dibandingkan dengan siswa yang diajar menggunakan strategi menulis konventional. Kata Kunci : kemampuan menulis, strategi “PLEASE”, strategi menulis konvensional. This research was aimed at investigating whether there was a significant difference on writing competency between the students who were taught by using “PLEASE” strategy and those who were taught by using conventional writing strategy. This research was an experimental research with Post-test Only Control Group Design. The population of this research was the tenth grade students of SMA Negeri 1 Sukasada in academic year 2016/2017 with the sample of 44 students who were selected through random sampling technique. The data were collected by using writing competency test. The obtained data were analyzed by using t-test assisted with SPSS 19.0. The result of the research showed that there was a significant difference on writing competency between the students who were taught by using “PLEASE” strategy and those who were taught by using conventional writing strategy (tobs = 12.506, p < 0.05) in which the students who were taught by using “PLEASE” strategy achieved better in writing competency than those who were taught by conventional writing strategy.keyword : conventional writing strategy, “PLEASE” strategy, writing competency